Early Transcriptome Differences Between Pre-Infected and Naïve Kid Goats Infected With Haemonchus contortus - Aboshady, Hadeer M.; Félicité, Yoann; Hira, Julien; Barbier, Claude; Bambou, Jean-Christophe (Frontiers in Veterinary Science, 2022)
In small ruminant production, gastrointestinal nematode (GIN) infection is one of the major causes of economic losses. The aim of this study was to compare the abomasal mucosa transcriptome of naïve and pre-infected goats at early time points after Haemonchus contortus infection, in order to identify different pathways and upstream regulators involved in the host immune response. Naïve and pre-infected Creole kids were orally infected with 10,000 H. contortus infective larvae (L3), and abomasal mucosa was sampled at 0, 4 and 6 days post-infection (dpi). At 6 dpi, all the animals were slaughtered to perform parasite burden counts. The mean number of L4 recovered in naïve kids was more than twice as high as that recovered in the pre-infected ones (5860 and 2474 respectively, P < 0.001). RNAseq analysis showed a number of differentially expressed genes (DEG) very low for both naïve and pre-infected animals when comparing day 0 versus day 4 post-infection. A total of 2237 and 3206 DEGs were identified comparing 0 versus 6 dpi in naïve and pre-infected animals, respectively. Interestingly, only 18 DEGs were found for the comparison of pre-infected versus naïve animals at 6 dpi. Ingenuity pathway analysis (IPA) showed that several immune responses were activated in pre-infected compared with naïve animals at 0 and 4 dpi such as Th2 and Th1 pathways, natural killer cell, B cell receptor, IL-2 and IL-15 signaling. On the other hand, both naïve and pre-infected animals showed activation for those pathways comparing 6 versus 0 dpi, with no difference between them. Similar pattern was recorded for upstream regulator genes which were related to immunity like TNF, IL1β, IL2, IL5, TGFβ1, IFN, TCR, IL18, IL6 and IL4. Our results showed that at 0 and 4 dpi the immune response was activated towards Th1 and Th2 pathways in pre-infected kids compared to the naïve ones, however the same immune response was developed in naïve kids as earlier as 6 dpi. We conclude that repeated H. contortus infection in kid goats induced a concomitant early activation of a Th1 and Th2 immune response resulting in the regulation of worm establishment.